Collagen XVII: A Shared Antigen in Neurodermatological Interactions? - Allan Seppänen (Clinical and Developmental Immunology)
Collagen XVII is a nonfibril-forming transmembrane collagen, which functions as both a matrix protein and a cell-surface receptor. It is particularly copious in the skin, where it is known to be a structural component of hemidesmosomes. In addition, collagen XVII has been found to be present in the central nervous system, thus offering an explanation for the statistical association between bullous pemphigoid, in which autoimmunity is directed against dermal collagen XVII, and neurological diseases. In support of the hypothesis that collagen XVII serves as a shared antigen mediating an immune response between skin and brain, research on animal and human tissue, as well as numerous epidemiological and case studies, is presented.